External technology sourcing: The effect of uncertainty on governance mode choice - van de Vrande, Vareska; Vanhaverbeke, Wim; Duysters, Geert (Journal of Business Venturing, 2009)
External knowledge sourcing is increasingly important for corporate entrepreneurship. In this study, we examine the effect of external and relational uncertainty on the governance choice for inter-organizational technology sourcing. We develop a number of hypotheses about the impact of environmental turbulence, technological newness, technological distance and prior cooperation on the choice between different governance modes. Data about external technology sourcing transactions in the pharmaceutical industry do not provide evidence for a continuum from less to more integrated sourcing modes. However, we find that the ranking depends on the type of uncertainty, indicating that firms tackle different types of uncertainty with different governance modes.